Analisis Opini Publik tagar #JanganJadiDosen pada media sosial X (Twitter) - Mawaddah, Mawaddah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study aims to analyze the dynamics of public opinion formed through the hashtag #JanganJadiDosen on the social media platform X (formerly Twitter). The hashtag emerged as an expression of dissatisfaction with the welfare conditions of lecturers in Indonesia, particularly concerning low income, excessive workload, and the lack of recognition for the intellectual contributions of academics. Using a descriptive qualitative approach with a netnographic method, this research explores data from user interactions on social media over a specific period with the assistance of the digital monitoring tool Brand24. The findings show that the majority of sentiments associated with this hashtag are negative and reflect widespread public concern. The analysis also reveals that social media is not merely a channel for disseminating information, but an active agent in constructing social realities and shaping public opinion through emotionally charged, participatory, and viral discourses. Within the framework of intermedia agenda setting theory, this phenomenon demonstrates how social media can precede mainstream media in setting the news agenda.Therefore, the #JanganJadiDosen hashtag serves as concrete evidence that social media holds strategic power in articulating social criticism and shaping collective perceptions of professional and higher education issues in Indonesia. These findings are essential to consider in the formulation of policies and decision-making processes that are more responsive to public sentiment.